Bodmin Moor : an archaeological survey. - Herring, Peter (Peter C.); Sharpe, Adam; Smith, John R.; Giles, Colum; Johnson, Nicholas, 1950- (Archaeological report (English Heritage), 2014)
"Bodmin Moor is an upland landscape, heavily protected, farmed extensively and with an increasingly light touch, and enjoyed by many as a retreat from busier modern worlds. But it is also a place of industry and the home of busy agricultural communities. Well-preserved remains of streamworking, mining, quarrying, clay working, turf cutting and more intensive farming were subjected to archaeological survey and historical research as part of the wider-ranging survey partly covered in the first volume (on prehistoric and medieval landscapes). Supplementing the survey text are aerial photographs and detailed line drawings, mainly plans and elevations, but also reconstructions of sites and schematic representations of processes as well as large-scale maps of key areas"--Publisher description.